IKTIKAD BAIK DAN TANGGUNG JAWAB PARA PIHAK DALAM PERJANJIAN KREDIT PERBANKAN DI BANK PERKREDITAN RAKYAT ABC (STUDI KASUS PUTUSAN PENGADILAN TINGGI BANTEN NO. 32/PDT/2016/PT BTN) - I Made Suri Pandhu; Imelda Martinelli (Jurnal Hukum Adigama, 2021)
One of the main banking functions is acting as an intermediary between a financially surplus party and a deficit party. Businessman uses banking loan facilities to fund their business. However, not all of business can grow as expected. On the event of  its debtor facing lose, bank will be impacted. Both parties must  overcome its bad debts problem pursuant to their loan agreement. This research uses normative methods to analyze Tangerang Court’s verdict No. 749/Pdt.G/2014/PN TNG which was concurred by Banten High Court through verdict No. 32/PDT/2016/PT BTN. The courts rule out  rural bank BPR (Bank Perkreditan Rakyat) ABC’s lawsuit against its debtor. Problem statement of this research is: how are good faith and responsibilities of both parties on banking loan agreement? It is found that Debtor experienced financial difficulties on their second loan. Debtor then requested loan restructuring. BPR ABC approved the request by  initiating addendum to loan agreement  to  extend  repayment period and to provide additional loan. However, only  3 months after  the restructuring, Debtor was unable  to fulfill his monthly installment as stated on loan agreement. Debtor was reluctant to discuss her loan problem. Therefore BPR ABC filed lawsuit. In the court, judges did not accept Debtor’s business downturn as valid reason for Debtor not to fulfill repayment schedule.  Writer concludes Debtor did not act in good faith and tried to avoid his responsibility. BPR ABC should improve its capability to asses  character and business prospect of its debtor.